Proposal of A Conceptual Model of The Customer Experience in The Experiential Leasure World Through Littérature: Attraction, Satisfaction and Loyalty - Yasmine LEBBADI; Mostafa ABAKOUY (Communications of International Proceedings, 2022)
Pine and Gilmore (1999), founders of the concept of experiential marketing, announce a new economic era, that of experience. This era is marked by the fact that consumers are thirsty for extraordinary, intense and memorable consumption experiences (Holbrook and Hirschman 1982). On the business side, they now use the product as an accessory and the experience as the main object of consumption (Pine & Gilmore 1999). Studies on the world of experiential leisure explain that it is by definition activities that are out of the ordinary, that one does not want to experience several times and whose customers have high and confused expectations at the same time ( Firat & Dholakia, 1998). The purpose of our article is to shed light precisely on the specificities of the customer experience in experiential leisure and to supply the literature with a conceptual model that explains the process of attraction, satisfaction and customer loyalty in the domain in question.
Keywords: Customer experience; experiential leisure; attraction; satisfaction; loyalty.